Post-exercise Hot Water Immersion Elicits Heat Acclimation Adaptations That Are Retained for at Least Two Weeks - Zurawlew, Michael J.; Mee, Jessica A.; Walsh, Neil P. (Frontiers in Physiology, 2019)
Heat acclimation by post-exercise hot water immersion (HWI) on six consecutive days reduces thermal strain and improves exercise performance during heat stress. However, the retention of adaptations by this method remains unknown. Typically, adaptations to short-term, exercise-heat-acclimation (< 7 heat exposures) decay rapidly and are lost within 2 weeks. Short-term protocols should therefore be completed within 2 weeks of relocating to the heat; potentially compromising pre-competition/deployment training. To establish whether adaptations from post-exercise HWI are retained for up to 2 weeks, participants completed a 40-min treadmill run at 65% V̇O2max in the heat (33°C, 40% RH) before (PRE) and 24 h after (POST) the HWI intervention (n = 13) and then at 1 week (WK 1) and 2 weeks (WK 2) after the HWI intervention (n = 9). Heat acclimation involved a 40-min treadmill run (65% V̇O2max) on six consecutive days in temperate conditions (20°C), followed by ≤ 40 min HWI (40°C). Post-exercise HWI induced heat acclimation adaptations that were retained for at least 2 weeks, evidenced by reductions from PRE to WK 2 in: resting rectal core temperature (Tre, -0.36 ± 0.25°C), Tre at sweating onset (-0.26 ± 0.24°C) and end-exercise Tre (-0.36 ± 0.37°C). Furthermore, mean skin temperature (-0.77 ± 0.70°C), heart rate (-14 ± 10 beats·min-1), rating of perceived exertion (-1 ± 2) and thermal sensation (-1 ± 1) were reduced from PRE to WK 2 (P < 0.05). However, PRE to POST changes in total hemoglobin mass, blood volume, plasma volume, the drive for sweating onset, sweating sensitivity and whole body sweating rate did not reach significance (P > 0.05). As such, the reduction in thermal strain during exercise-heat stress appears likely due to the reduction in resting Tre evident at POST, WK 1 and WK 2. In summary, 6 days of post-exercise HWI is an effective, practical and accessible heat acclimation strategy that induces adaptations, which are retained for at least 2 weeks. Therefore, post-exercise HWI can be completed during an athlete’s pre-taper phase and does not suffer from the same practical limitations as short-term, exercise-heat-acclimation.